The Market’s View on Accounting Classifications for Asset Securitizations - Minkwan Ahn (International Journal of Financial Studies, 2023)
Prior research has examined how investors view asset securitizations, and shows that investors treat securitizations as borrowings, even when GAAP treats them as sales. Upon the adoption of two new accounting standards relating to securitizations, some off-balance-sheet securitized assets were consolidated back onto firms’ balance sheets. This study investigated how investors viewed assets that firms consolidated under the new standards and those that firms left unconsolidated. I found that investors differentiated between these two types of securitizations, treating the consolidated assets as borrowings and the unconsolidated assets as sales. I conclude that the new accounting standards are more consistent with equity investors’ views of securitizations. I also found that, for the consolidated assets, investors did not distinguish between securitizations going through two different accounting structures. Lastly, this study provides evidence on one information channel that investors use to distinguish between securitizations that may have the economic substance of borrowings versus sales.